If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2n = 3n + -4 Reorder the terms: 2n = -4 + 3n Solving 2n = -4 + 3n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-3n' to each side of the equation. 2n + -3n = -4 + 3n + -3n Combine like terms: 2n + -3n = -1n -1n = -4 + 3n + -3n Combine like terms: 3n + -3n = 0 -1n = -4 + 0 -1n = -4 Divide each side by '-1'. n = 4 Simplifying n = 4
| -1.5x^2+33x-75=52.50 | | i-(1+i)=-1 | | 3x-(5x+4)=7x-40 | | (6+x)/2=11.5 | | 58=8x+2 | | 4(2x-1)=3x+6 | | m=-16-m | | x^3+8x^2+12x-16=0 | | i-(1+i)= | | x^3+5x^2+3x-6=0 | | 6-5x=4x-12 | | 6x+4=4x+7 | | 2/3q-q=14 | | 43.5*1/3 | | 5s+4=22 | | 43.50(1/3) | | -11-5x=2(3x-1) | | -15=y-(-14) | | x-13=22-17 | | 4=k*6 | | 5=16t^2 | | 1/12-9=12 | | 4d+12=20 | | (1/64)x=1/512 | | 7-2u=3(u-1) | | 4x+8x+10xy+(9xy-5-9)= | | x+27=911 | | 5n+2/3+7=9 | | 1/12+12=17+3 | | 6h-12=4h+6 | | 5-8n/3=2n | | x^2+h=32 |